Assessment of health-related quality of life in the elderly on maintenance hemodialysis - Mohd Shahrin, Fatin Izzaty; Omar, Noraida; Mat Daud, Zulfitri 'Azuan; Zakaria, Nor Fadhlina (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2019)
Introduction: Health-related quality of life (HRQOL) is one of the main indicators of health and wellbeing among dialysis patients which has attracted mounting interest in recent years in the initiation of intervention measures. Thus, this study aimed to determine the correlations between socio-demographic factors and medical characteristics with HRQOL among elderly on maintenance hemodialysis (HD). Methods: A cross-sectional study was conducted in nine HD centers in Selangor. Socio-demographic data and HRQOL were assessed using structured questionnaire and Kidney Disease Quality of Life Instrument (KDQOL-36), respectively whilst medical profile and laboratory data were collected from subjects’ medical record. Results: The mean age of subjects was 67±6 years where majority (57%) of the subjects was on maintenance HD for less than 5 years. The mean physical component summary and mental component summary scores were 33.89±11.83 and 50.23±8.88, respectively. Symptoms/problems subscale, effects of kidney disease on daily life subscale and burden of kidney disease subscale scores were 73.37±17.01, 72.63±19.74 and 54.62±30.42, respectively. There was a significant correlation between serum sodium with physical component summary (r=0.237, p<0.01) and symptoms/problems subscale (r= 0.245, p<0.01). Conclusion: Subjects perceived their mental health better than physical health but felt burdened by kidney disease the most. Serum sodium was found to be positively associated with physical functioning and symptoms/problems subscales. There is a need for routine assessment on HRQOL and appropriate intervention to enhance the quality of life among elderly on HD.